Multi objective performance analysis of nanofiltration process to loading parameters by response surface approach - Tansel, Berrin; Dizge, Nadir (Elsevier Science Bv, 2011)
Response surface analysis was used to investigate membrane performance in relation to operating variables for removing zinc by nanofiltration. The control variables were selected as transmembrane pressure (2 and 4 bars), membrane type (NF 90 and NF 270), and zinc concentration in the feed solution (10.250 and 500 mg/L). Effects and interactions of the control variables were investigated in relation to quality of permeate, total membrane resistance, and the overall process performance, which was defined as the product of zinc concentration and total membrane resistance. The system performance was also evaluated in relation to membrane stress, which was defined as the product of influent zinc concentration and transmembrane pressure. The response surfaces, visualized by 3D graphics, show that there are optimum conditions for each membrane when system performance was defined to improve both the permeate quality and maintain a high flux level. The response surface equations provided relative significance of the variables on the membrane performances for the NF 90 membrane and the more permeable NF 270 membrane in terms of effluent quality, percent rejection, and membrane resistance. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Nanofiltration; Heavy metal; Factorial design; Limiting flux; Response surface; Zinc; Ionic load; Membrane loading